Pore‐scale and multiscale numerical simulation of flow and transport in a laboratory‐scale column. Issue 2 (19th February 2015) - Scheibe, Timothy D.; Perkins, William A.; Richmond, Marshall C.; McKinley, Matthew I.; Romero‐Gomez, Pedro D. J.; Oostrom, Mart; Wietsma, Thomas W.; Serkowski, John A.; Zachara, John M.
Abstract: Pore‐scale models are useful for studying relationships between fundamental processes and phenomena at larger (i.e., Darcy) scales. However, the size of domains that can be simulated with explicit pore‐scale resolution is limited by computational and observational constraints. Direct numerical simulation of pore‐scale flow and transport is typically performed on millimeter‐scale volumes at which X‐ray computed tomography (XCT), often used to characterize pore geometry, can achieve micrometer resolution. In contrast, laboratory experiments that measure continuum properties are typically performed on decimeter‐scale columns. At this scale, XCT resolution is coarse (tens to hundreds of micrometers) and prohibits characterization of small pores and grains. We performed simulations of pore‐scale processes over a decimeter‐scale volume of natural porous media with a wide range of grain sizes, and compared to results of column experiments using the same sample. Simulations were conducted using high‐performance codes executed on a supercomputer. Two approaches to XCT image segmentation were evaluated, a binary (pores and solids) segmentation and a ternary segmentation that resolved a third category (porous solids with pores smaller than the imaged resolution). We used a multiscale Stokes‐Darcy simulation method to simulate the combination of Stokes flow in large open pores and Darcy‐like flow in porous solid regions. Flow and transport simulations based on the binary segmentation were inconsistent with experimental observations because of overestimation of large connected pores. Simulations based on the ternary segmentation provided results that were consistent with experimental observations, demonstrating our ability to successfully model pore‐scale flow over a column‐scale domain. Key Points: We successfully simulated pore‐scale flow over a column‐scale domain Simulation results matched experimental observations well Segmentation of X‐ray image data is a critical step in accurate simulation